Kajian Lama Penyimpanan Asam Pedas Ikan Lele Menggunakan Standing Pouch Aluminium Foil - Afiqah, Nurul; Hartanti, Lucky; Rahayuni, Tri (Agriculture Faculty, 2024)
Catfish (Clarias sp.) is a potential freshwater fish to be developed into traditional West Kalimantan food, namely Asam Pedas. The products short shelf life is only about 1-2 days, so the right packaging technology is needed to extend its shelf life. This research uses catfish as the main ingredient and aluminium foil standing pouch packaging. This study aimed to determine the physicochemical characteristics of Asam Pedas Ikan Lele in aluminium foil standing pouch packaging during storage. The length of storage used was 0, 5, 10, 15, 20, and 25 days. The parameters observed were pH value, thiobarbituric acid (TBA), total plate count (TPC), and sensory in color, aroma, and texture. The results showed that the length of storage significantly affected the pH value. The total number of microbes that meet the maximum limit of microbial contamination in food is stored for 15 days at 3,1 x 104 CFU/ml. Sensory results showed that the length of storage on days 5 and 10 was not significantly different, while the length on 15, 20, and 25 days was significantly different in color, aroma, and texture.